Transverse Expansion and Stability after Segmental Le Fort I Osteotomy versus Surgically Assisted Rapid Maxillary Expansion: a Systematic Review - Thomas Starch-Jensen; Tue Lindberg Blæhr (Stilus Optimus, 2017)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in transverse skeletal and dental arch expansion and relapse after segmental Le Fort I osteotomy versus surgically assisted rapid maxillary expansion. Material and Methods: A MEDLINE (PubMed), Embase and Cochrane library search in combination with a hand-search of relevant journals was conducted by including human studies published in English from January 1, 2000 to June 1, 2016. Results: The search provided 130 titles and four studies fulfilled the inclusion criteria. All the included studies were characterized by high risk of bias and meta-analysis was not possible due to considerable variation. Both treatment modalities significantly increase the transverse maxillary skeletal and dental arch width. The transverse dental arch expansion and relapse seems to be substantial higher with tooth-borne surgically assisted rapid maxillary expansion compared to segmental Le Fort I osteotomy. The ratio of dental to skeletal relapse was significantly higher in the posterior maxilla with tooth-borne surgically assisted rapid maxillary expansion. Moreover, a parallel opening without segment tilting was observed after segmental Le Fort I osteotomy. Conclusions: Maxillary transverse deficiency in adults can be treated successfully with both treatment modalities, although surgically assisted rapid maxillary expansion seems more effective when large transverse maxillary skeletal and dental arch expansion is required. However, considering the methodological limitations of the included studies, long-term randomized studies assessing transverse skeletal and dental expansion and relapse with the two treatment modalities are needed before definite conclusions can be provided.